Polyol-mediated synthesis of ZnO nanoparticle-assembled hollow spheres/nanorods and their photoanode performances - Kim, Soon Wook; Nguyen, Tri Khoa; Van Thuan, Doan; Dang, Dinh Khoi; Hur, Seung Hyun; Kim, Eui Jung; Hahn, Sung Hong (The Korean journal of chemical engineering, 2017)
ZnO nanoparticle-assembled hollow spheres (raspberry-like) and elliptical nanorods (rice-like) were synthesized via a facile polyol process. Employing ethylene glycol as a polyol led to a ZnO nanoparticle-assembled hollow sphere structure, while diethylene glycol resulted in an elliptical nanorod structure. The ZnO hollow spheres had a higher Brunauer-Emmett-Teller (BET) surface area, better dye adsorption, more incident light trapping, and lower defect density than the ZnO elliptical nanorods. The ZnO hollow sphere-based dye-sensitized solar cells (DSSCs) exhibited a three-times higher current density than the ZnO elliptical nanorod-based DSSCs.